Contrast Sensitivity Is a Significant Predictor of Performance in Rifle Shooting for Athletes With Vision Impairment - Allen, Peter M.; Ravensbergen, Rianne H. J. C.; Latham, Keziah; Rose, Amy; Myint, Joy; Mann, David L. (Frontiers in Psychology, 2018)
Purpose: In order to develop an evidence-based, sport-specific minimum impairment criteria for the sport of vision-impaired (VI) shooting, this study aimed to determine the relative influence of losses in visual acuity (VA) and contrast sensitivity (CS) on shooting performance. Presently, VA but not CS is used to determine eligibility to compete in VI shooting. Methods: Elite able-sighted athletes (n=27) shot under standard conditions with their habitual vision, and with their vision impaired by the use of simulation spectacles (filters which reduce both VA and CS) and refractive blur (lenses which reduce VA with less effect on CS). Habitual shooting scores were used to establish a cut-off in order to determine when shooting performance was 'below expected' in the presence of vision impairment. Logistic regression and decision tree analyses were then used to assess the relationship between shooting performance and visual function. Results: Mild reductions in VA and/or CS did not alter shooting performance, with greater reductions required for shooting performance to fall below habitual levels (below 87% of normalised performance). Stepwise logistic regression selected CS as the most significant predictor of shooting performance, with VA subsequently improving the validity of the model. In an unconstrained decision tree analysis, CS was selected as the sole criterion (80%) for predicting 'below expected' shooting score. Conclusions: Shooting performance is better predicted by losses in CS than by VA. Given that it is not presently tested during classification, the results suggest that CS is an important measure to include in testing for the classification of vision impairment for athletes competing in VI shooting.